New modalities of allergen immunotherapy - Manish Ramesh; Merhunisa Karagic (Taylor & Francis Group, 2018)
Allergen immunotherapy is a rapidly evolving field. Although subcutaneous immunotherapy has been practiced for over a hundred years, improved understanding of the underlying immunological mechanisms has led to the development of new, efficacious and better tolerated allergen-derivatives, adjuvants and encapsulated allergens. Diverse routes of allergen immunotherapy - oral, sublingual, epicutanoeus and intralymphatic - are enabling immunotherapy for anaphylactic food allergies and pollen-food allergy syndrome, while improving the tolerability and effectiveness of aeroallergen immunotherapy. The addition of Anti-IgE therapy decreases adverse effects of subcutaneous and oral immunotherapy.